Rapid and Oriented Immobilization of Laccases on Electrodes via a Methionine-Rich Peptide - Cui, Haiyang; Zhang, Lingling; Söder, Dominik; Tang, Xiaomei; Davari, Mehdi D; Schwaneberg, Ulrich (ACS catalysis, 2021)
Different from other laccases, copper efflux oxidase (CueO) from Escherichia coli possesses an additional methionine-rich segment (MetRich), which is generally considered to be detrimental to its oxidase activity. Herein, we reveal that MetRich plays an important role in rapid immobilization of CueO on electrodes by studying the adsorption and bioelectrocatalysis behaviors of CueO, a truncated CueO (ΔMetRich CueO), and a serine-rich substituted CueO (SerRich CueO). Atomic molecular dynamics (MD) simulations demonstrate that the synergistic effect of π–π stacking and hydrophobic interactions contribute to the high affinity of MetRich to carbon nanotubes. Considering that the location of the electron acceptor (i.e., T1 Cu active site) in the family of laccases is close to the C-terminus, MetRich fused to another bacterial laccase, spore coat protein A (CotA) from Bacillus licheniformics, is found to endow CotA with the properties of rapid and oriented adsorption at the electrode surface. The finding and validation make MetRich a valuable binding motif for the rapid immobilization and high performance of laccases and perhaps other oxidoreductases in bioelectrocatalytic applications.